Prepared omadacycline for injection: Nine-day stability and sterility in an elastomeric pump. (November 2022) - Bower, Jason; Wright, Kelly; Burdette, Jason
Objective: To investigate compatibility, stability, and microbiologic risk of omadacycline 1 mg/mL when prepared in an elastomeric infusion pump and stored under refrigeration for 9 days based upon requests for information from healthcare providers. Methods: Omadacycline was reconstituted to 1 mg/mL with sodium chloride 0.9% w/v or dextrose 5% w/v in SMARTeZ ® elastomeric infusion pumps and refrigerated for up to 9 days. Samples were taken daily and tested for appearance, pH, osmolality, chemical composition, and particulate matter. For a microbial challenge study, the pumps were spiked with a challenge microorganism ( Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Candida albicans, or Aspergillus brasiliensis ) and samples were plated daily for 9 days to assess microbial survival. Results: Appearance, pH, osmolality, percent label claim, and particulate matter results remained essentially unchanged for omadacycline solutions in either diluent over the 9-day study. No > 0.5-log day-to-day increases in the challenge-microorganism populations were measured in diluted omadacycline pumps or positive controls. With omadacycline, no growth was seen for S. aureus or E. coli in either diluent, nor for P. aeruginosa in dextrose 5% w/v. Reduction of C. albicans and A. brasiliensis populations over time was similar between omadacycline solutions and positive controls. Conclusion: After reconstitution, omadacycline for injection was stable and remained within specifications for use for up to 9 days when refrigerated.